Matrix Metalloproteinase Inhibition in Atherosclerosis and Stroke - D. Roycik, M.; S. Myers, J.; G. Newcomer, R.; A. Sang, Q.-X. (Current Molecular Medicine, 2013)
Matrix metalloproteinases (MMPs) are a family of tightly regulated, zinc-dependent proteases that degrade extracellular matrix (ECM), cell surface, and intracellular proteins. Vascular remodeling, whether as a function of normal physiology or as a consequence of a myriad of pathological processes, requires degradation of the ECM. Thus, the expression and activity of many MMPs are up-regulated in numerous conditions affecting the vasculature and often exacerbate vascular dysfunction. A growing body of evidence supports the rationale of using MMP inhibitors for the treatment of cardiovascular diseases, stroke, and chronic vascular dementia. This manuscript will examine promising targets for MMP inhibition in atherosclerosis and stroke, reviewing findings in preclinical animal models and human patient studies. Strategies for MMP inhibition have progressed beyond chelating the catalytic zinc to functional blocking antibodies and peptides that target either the active site or exosites of the enzyme. While the inhibition of MMP activity presents a rational therapeutic avenue, the multiplicity of roles for MMPs and the non-selective nature of MMP inhibitors that cause unintended side-effects hinder full realization of MMP inhibition as therapy for vascular disease. For optimal therapeutic effects to be realized, specific targets for MMP inhibition in these pathologies must first be identified and then attacked by potent and selective agents during the most appropriate timepoint.
Keywords: matrix metalloproteinase inhibitors